Impact of perceived inappropiate cardiopulmonary resuscitation on emergency clinicians' intention to leave the job: Results from a cross-sectional survey in 288 centres across 24 countries. (January 2021) - Druwé, Patrick; Monsieurs, Koenraad G.; Gagg, James; Nakahara, Shinji; Cocchi, Michael N.; Élő, Gábor; van Schuppen, Hans; Alpert, Evan Avraham; Truhlář, Anatolij; Huybrechts, Sofie A.; Mpotos, Nicolas; Paal, Peter; et al.
Abstract: Introduction: Cardiopulmonary resuscitation (CPR) in patients with a poor prognosis increases the risk of perception of inappropriate care leading to moral distress in clinicians. We evaluated whether perception of inappropriate CPR is associated with intention to leave the job among emergency clinicians. Methods: A cross-sectional multi-centre survey was conducted in 24 countries. Factors associated with intention to leave the job were analysed by conditional logistic regression models. Results are expressed as odds ratios with 95% confidence intervals. Results: Of 5099 surveyed emergency clinicians, 1836 (36.0%) were physicians, 1313 (25.7%) nurses, 1950 (38.2%) emergency medical technicians. Intention to leave the job was expressed by 1721 (33.8%) clinicians, 3403 (66.7%) often wondered about the appropriateness of a resuscitation attempt, 2955 (58.0%) reported moral distress caused by inappropriate CPR. After adjustment for other covariates, the risk of intention to leave the job was higher in clinicians often wondering about the appropriateness of a resuscitation attempt (1.43 [1.23−1.67]), experiencing associated moral distress (1.44 [1.24−1.66]) and who were between 30−44 years old (1.53 [1.21−1.92] compared to <30 years). The risk was lower when the clinician felt valued by the team (0.53 [0.42−0.66]), when the team leader acknowledged the efforts delivered by the team (0.61 [0.49−0.75]) and in teams that took time for debriefing (0.70 [0.60−0.80]). Conclusion: Resuscitation attempts perceived as inappropriate by clinicians, and the accompanying moral distress, were associated with an increased likelihood of intention to leave the job. Interprofessional collaboration, teamwork, and regular interdisciplinary debriefing were associated with a lower risk of intention to leave the job. ClinicalTrials.gov; No.: NCT02356029